Mixing and matching N,N- and N,O-chelates in anionic Mg(i) compounds: synthesis and reactivity with RN=C=NR and CO - O'Reilly, Andrea; Haynes, Matthew D.; Turner, Zoë R.; McMullin, Claire L.; Harder, Sjoerd; O'Hare, Dermot; Fulton, J. Robin; Coles, Martyn P. (Chemical Communications, 2024)
Reduction of [Mg(NON)]2 ([NON]2− = [O(SiMe2NDipp)2]2−, Dipp = 2,6-iPr2C6H3) affords Mg(i) species containing NON- and NNO-ligands ([NNO]2− = [N(Dipp)SiMe2N(Dipp)SiMe2O]2−). The products of reactions with iPrN C NiPr and CO are consistent with the presence of reducing Mg(i) centres. Extraction with THF affords [K(THF)2]2[(NNO)Mg-Mg(NNO)] with a structurally characterised Mg-Mg bond that was examined using density functional theory.
CRIS-Team Scopus Importer:2024-07-12